Investing in Late-Life Brain Capital. Issue 3 (18th May 2022) - Dawson, Walter D; Smith, Erin; Booi, Laura; Mosse, Maia; Lavretsky, Helen; Reynolds, Charles F; Cummings, Jeffrey; Brannally, Patrick; Hynes, William; Lenze, Eric J; Manes, Facundo; Ayadi, Rym; et al.
Abstract: Within many societies and cultures around the world, older adults are too often undervalued and underappreciated. This exacerbates many key challenges that older adults may face. It also undermines the many positive aspects of late life that are of tremendous value at both an individual and societal level. We propose a new approach to elevate health and well-being in late life by optimizing late-life Brain Capital. This form of capital prioritizes brain skills and brain health in a brain economy, which the challenges and opportunities of the 21st-century demands. This approach incorporates investing in late-life Brain Capital, developing initiatives focused on building late-life Brain Capital.